2022
DOI: 10.1177/1934578x221141276
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Could Improve Gestational Diabetes by Targeting Genes Involved in Nutrient Metabolism, Oxidative Stress, Inflammation, and the WNT/β-Catenin/GSK3β Signaling Pathway

Abstract: This study aimed to evaluate the effect in female rats of 6 weeks of ginger consumption on gestational diabetes by assessing glucose and lipid metabolism, oxidative damage, inflammation, and the WNT/β-catenin/glycogen synthase kinase-3 beta (GSK3β) signaling pathway. In this study, 40 adult female rats were divided into 4 equal groups as follows: pregnant rats, pregnant rats with diabetes, pregnant rats consuming ginger, and pregnant rats with diabetes consuming ginger. Induction of diabetes on day 0 of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Specifically, increase in antioxidant mechanisms serves as the protective mechanisms for sperm in the testicular microenvironment and enhances spermatogenesis in the testes [ 13 , 24 , 28 , 78 ]. In addition, previous studies have also shown that HFD and ethanol downregulated Nrf2 testicular expression and improving its expression are associated with enhancing testosterone production and its serum level [ 3 , 28 , 79 ]. Our results clearly showed that pretreatment and treatment with garlic enhance the expression of Nrf2 and antioxidant enzymes activity and decrease the level of MDA in the testicular tissue of obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, increase in antioxidant mechanisms serves as the protective mechanisms for sperm in the testicular microenvironment and enhances spermatogenesis in the testes [ 13 , 24 , 28 , 78 ]. In addition, previous studies have also shown that HFD and ethanol downregulated Nrf2 testicular expression and improving its expression are associated with enhancing testosterone production and its serum level [ 3 , 28 , 79 ]. Our results clearly showed that pretreatment and treatment with garlic enhance the expression of Nrf2 and antioxidant enzymes activity and decrease the level of MDA in the testicular tissue of obese rats.…”
Section: Discussionmentioning
confidence: 99%